2011
DOI: 10.1111/j.1749-7345.2010.00443.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Maturation Diets on the Reproductive Output of the White‐striped Cleaner Shrimp, Lysmata amboinensis

Abstract: Aquaculture production of the cleaner shrimp Lysmata amboinensis, a high‐valued marine ornamental, has been problematic because of prolonged larval development punctuated by periods of mortality. Broodstock maturation diets have been shown to affect fecundity and offspring quality and early survival. The common practice in shrimp culture is the use of fresh frozen foods supplemented with artificial diets. The objective of the study was to identify a suitable maturation diet (natural or artificial) for L. amboi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…Growth in the 2-month study was also satisfactory, and although towards the lower end, still within the previously observed range for the species of 7-11% (Tziouveli et al 2011). There were, however, marked differences in the reproductive output among shrimp in different dietary treatment groups.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Growth in the 2-month study was also satisfactory, and although towards the lower end, still within the previously observed range for the species of 7-11% (Tziouveli et al 2011). There were, however, marked differences in the reproductive output among shrimp in different dietary treatment groups.…”
Section: Discussionsupporting
confidence: 77%
“…Embryo hatchability in the current study improved significantly when DHA-boosted Artemia were fed to L. amboinensis broodstock. In a previous comparison of maturation diets for L. amboinensis, a commercial pellet (Kuruma prawn diet, Ebi Star, Higashimaru, Japan) yielded high larval production (Tziouveli et al 2011), and when combining those results with the findings of this study, elevated DHA concentrations of 11-14% in broodstock diets intended for L. amboinensis are recommended. During the study, it was noted that shrimp egg production and attachment proceeded despite the low concentration of ARA and EPA in the diets, and in shrimp fed ''unenr'' Artemia of a DHA absence as well, and perhaps suggests a minimal role of these n-6 and n-3 HUFAs during this phase of reproduction.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…No complete profile description was found for L. opalescens (Tziouveli et al, 2011) and no data was found for L. reynaudii. The slight differences ob-served with our study may be due to variations in geographical provenance, water temperature and salinity, diet season of catch, gender, sexual maturity (Ozogul et al, 2008) and analytical methodology.…”
mentioning
confidence: 92%